2015
DOI: 10.1155/2015/503918
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Liothyronine on Electroconvulsive Therapy-Induced Memory Deficit in Patients with Major Depressive Disorder: A Double-Blind Controlled Clinical Trial

Abstract: Introduction and Objective. Despite the effectiveness of electroconvulsive therapy (ECT) in treating major depressive disorder (MDD), its cognitive side effects make it less popular. This study investigated the impact of liothyronine on ECT-induced memory deficit in patients with MDD. Methodology. This is a double-blind clinical trial, in which 60 patients with MDD who were referred for ECT were selected. The diagnosis was based on the criteria of DSM-IV-TR. Patients were divided randomly into two groups to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The ADRs to LT3 were not considered a primary outcome in any of the studies and only five reported specifically on palpitation, heart rate, and tremor, with the remainder only mentioning nonspecific ADRs (Supplementary Table S3). Remarkably, in none of these 12 studies did the association of LT3 result in ADRs (131)(132)(133)(134)(135)(136)(137)(138)(139)(140)143,144). A subsequent meta-analysis that included eight studies (five clinical trials described earlier plus three observational studies) failed to identify differences in ADRs in LT3 versus control patients (145).…”
Section: Clinical Trials In Which Liothyronine Therapy Was Used In Euthyroid Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ADRs to LT3 were not considered a primary outcome in any of the studies and only five reported specifically on palpitation, heart rate, and tremor, with the remainder only mentioning nonspecific ADRs (Supplementary Table S3). Remarkably, in none of these 12 studies did the association of LT3 result in ADRs (131)(132)(133)(134)(135)(136)(137)(138)(139)(140)143,144). A subsequent meta-analysis that included eight studies (five clinical trials described earlier plus three observational studies) failed to identify differences in ADRs in LT3 versus control patients (145).…”
Section: Clinical Trials In Which Liothyronine Therapy Was Used In Euthyroid Individualsmentioning
confidence: 99%
“…The LT3 has been used in patients with major depressive disorder as an adjuvant to the conventional treatment with antidepressants, even if the patients are euthyroid (Supplementary Table S3) (131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144). We identified 12 prospective clinical trials conducted between 1970s and 2018 (Supplementary Table S2) in which a regimen with LT3 was used.…”
Section: Clinical Trials In Which Liothyronine Therapy Was Used In Euthyroid Individualsmentioning
confidence: 99%
“… 46 , 47 One trial supplied insufficient data for quantitative synthesis, but described a significantly positive effect on global cognitive outcome (see E‐Table 2 in the Supplement). 48 …”
Section: Resultsmentioning
confidence: 99%
“…Three studies did not meet criteria for inclusion in our quantitative synthesis; however, two of these were small crossover trials, which reported a statistically significant effect on cognitive outcome 46,47 . One trial supplied insufficient data for quantitative synthesis, but described a significantly positive effect on global cognitive outcome (see E‐Table in the Supplement) 48 …”
Section: Resultsmentioning
confidence: 99%
“…A recent review has reported that the relationship between the years of education, and the neurocognitive effects of ECT had not been investigated (McClintock et al, 2014), and our study has added relevant evidence. Liothyronine has been reported to reduce the memory deficits following ECT in people with depression, but the relationship between hypothyroidism and the memory deficits has not been studied (Mohagheghi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%